Czy europejskie prawo do dobrej administracji przysługuje w Ukrainie? - Radyszewska, Ołesia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The article depicts the essence and peculiarities of the functioning of right to good administration in Ukraine and Member-States of EU, which is the subject of the study of Ukrainian and European administrative law doctrine. It has been established that good administration, as a subjective right, provides grounds for the effective enforcement of the rights of individuals. At the same time, maladministration is manifested in a functional sphere – the activities of national, regional and local ombudsmen and the European Civil Rights Ombudsman. It is stated that these concepts are basic for European and global administrative law and have direct influence on Ukrainian administrative law.
Does the European right to good administration exist in Ukraine?
Keywords: public administration; good administration; maladministration; European administrative law; right to good administration